Citizen Science as a Driver of Employee Engagement: A Case Study of the PENDAKI Program - Nunik Maharani; Janette Maria Pinariya (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2025)
This study examines how the PENDAKI program at PT Austindo Nusantara Jaya Tbk (ANJ) fosters employee engagement through citizen science. The main goal is to understand how it creates employee engagement within corporate sustainability efforts. The research draws on internal communication theories, highlighting the importance of information exchange for organizational efficiency, employee performance, motivation, and sustainability communication, which connects environmental issues with social values to promote sustainable practices. The study explores the question: â€œHow can citizen science through the PENDAKI program create employee engagement?â€. Using a qualitative descriptive case study approach, it focuses on the PENDAKI program at ANJ from 2019-2024. Data was collected through semi-structured interviews with management, conservation staff, and employee participants across different operational areas, along with documentary evidence like internal research and program evaluation reports. The findings show that PENDAKI fosters employee engagement through several pathways. Participation increased employee awareness and understanding of biodiversity and conservation efforts. Employees felt they were contributing to the company's sustainability goals and values. The program offered opportunities for skill development in species identification and documentation, and recognition for contributions, which motivated further participation. It also reduced silos between departments and encouraged collaboration towards a shared conservation objective. Additionally, the program positively impacted the company's external image and fostered employee pride. The study concludes that PENDAKI creates employee engagement by fostering a sense of purpose, providing skill development opportunities, and promoting a shared commitment to biodiversity conservation, highlighting the role of communication strategies in the success of such initiatives.